A ju jag eun ssi as - Carle, Eric 1929-2021 (Montessori CM, 2022)
A simple description of a flowering plant's life cycle through the seasons. Dazzlingly colorful collage illustrations and a simple but dramatic text tell the fascinating story of the life cycle of a flower in terms of the adventures of a tiny seed. Carried aloft by the autumn wind, the tiny seed, along with other bigger seeds, travels far over the world. the journey is perilous: one of the bigger seeds is burned by the sun another falls into the ocean still another is eaten by a bird. Even after those that are left have landed on fertile ground and begun to grow, danger is near: one small plant is stepped on one little flower is picked but the tiny seed keeps growing almost unnoticed. Young readers will cheer at the happy outcome of this exciting tale. And they will long remember the heartening message of the tiny seed's steadfast perseverance in the face of many hazards and obstacles until its final joyful success
Keywords: Plants / Juvenile literature; Seeds / Juvenile literature; Plant life cycles / Juvenile literature; Seeds / Dispersal / Juvenile literature; Bilderbuch